Halal Influencer and Content Creator Taxation: Obligations and the Mechanism for Calculating Presumptive Net Income - Dewi Nawal Fahira; Muhammad Ilyas Darussalam; Suparmin Suparmin; Agus Rojak Samsudin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
The development of digital technology has given rise to new professions such as content creators and YouTubers who earn income from digital economic activities, including AdSense and endorsement services. The emergence of these income sources has legal implications, particularly in taxation. This study aims to analyze the application of the Presumptive Net Income Calculation Norm (NPPN) at a rate of 50% on content creators’ income and to examine its fairness compared to the actual profit margins obtained. The research method employed is a case simulation, with the object of study being the income of an independent YouTuber derived from AdSense and endorsement activities. The findings indicate that the application of the 50% NPPN provides administrative convenience for taxpayers; however, it does not fully reflect real economic conditions due to the significant operational costs involved in digital content production. Furthermore, for Muslim content creators, tax obligations intersect with professional zakat obligations as a form of religious responsibility. The integration of professional zakat and taxation may serve as a normative solution for promoting fairness, particularly through zakat as a deduction from taxable income. Therefore, a more adaptive taxation approach is required, one that accommodates the characteristics of the digital economy while remaining aligned with principles of justice from a Sharia perspective.